A Janus photothermal layer and preparation method thereof, and evaporator

By etching the Ti3AlC2 precursor with a mixed liquid of LiF and HCl in the Janus film and adsorbing it on the fabric using the hydrogen bonding of MXene, combined with the use of a hydrophobic modifier, Janus with excellent light absorption and photothermal conversion capabilities was constructed. The photothermal layer solves the problems of poor light absorption capacity and low photothermal conversion efficiency in the prior art, and realizes efficient solar seawater desalination and stable salt crystal collection.

CN116479648BActive Publication Date: 2025-02-14SHENZHEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310249780.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-02-14
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

The existing Janus film preparation process is complex and has limited thickness, resulting in unsatisfactory heat insulation and heat insulation positions, affecting the evaporation efficiency and desalination rate. At the same time, MXene is easily oxidized in the air, resulting in poor light absorption capacity and low photothermal conversion efficiency.

Method used

The Ti3AlC2 precursor was etched with a mixture of LiF and HCl to obtain a single layer of Ti3C2TxMXene, and adsorbed it on the fabric through hydrogen bonding of MXene. Then, one side of the fabric was hydrophobic modified with a hydrophobic modifier. The Janus photothermal layer with asymmetric wetting is constructed.

Benefits of technology

The light absorption and photothermal conversion capabilities of the Janus photothermal layer are improved, the thermal management capabilities of the evaporator are enhanced, and the efficient solar seawater desalination is achieved, and the stability is maintained during long-term desalination operations are maintained, while the salt crystals can be collected.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116479648B_ABST
    Figure CN116479648B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solar desalination, and in particular to a Janus photothermal layer and a preparation method thereof, and an evaporator. The present invention etches a Ti3AlC2 precursor by using a mixed solution of LiF and HCl, and then ultrasonically peels off to obtain a single-layer Ti3C2T x MXene; then the hydrogen bonding effect of MXene is used to firmly adsorb MXene on the fabric, and then one side of the fabric is hydrophobically modified using a hydrophobic modifier to construct a Janus structure photothermal layer with asymmetric wettability, which has excellent light absorption and photothermal conversion capabilities; in addition, by constructing an evaporator with a suspension bridge structure using the Janus photothermal layer, it can be used for solar seawater desalination; the suspension bridge structure has good thermal management capabilities, and the evaporator can achieve efficient solar seawater desalination, and has good stability in long-term desalination operation, and can collect salt crystals while producing clean water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar seawater desalination, and in particular to a Janus photothermal layer and a preparation method thereof, and an evaporator. Background Art

[0002] Solar desalination can be broadly understood as a technology that uses solar energy as a driving energy source to produce fresh water. Solar desalination combines the most abundant solar energy resources with seawater resources, which can not only alleviate the shortage of fresh water resources in people's production process, but also indirectly contribute to the protection of the ecological environment because it generally does not consume non-renewable resources and does not produce harmful and toxic substances during the production process.

[0003] Ti 3 C 2 T x MXene was first reported by Yury et al. in 2011. 3 C 2 T x MXene materials have been widely studied and paid attention to due to their unique structure and properties, and have shown great application potential in piezoresistive pressure sensors, electromagnetic shielding, batteries, and supercapacitors.

[0004] Since 1991, Janus bifacial materials, introduced by PG de Gennes in his Nobel Prize lecture, have been widely used in oil-water separation, membrane distillation and solar-driven desalination.

[0005] However, the traditional Janus membrane preparation process is complicated and the thickness is limited, which makes the thermal insulation and heat insulation position unsatisfactory, affecting the evaporation efficiency and desalination rate. And MXene is easily oxidized in the air.

[0006] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a Janus photothermal layer and a preparation method and an evaporator thereof, aiming to solve the problems of poor light absorption capacity and low photothermal conversion efficiency of the existing photothermal layer.

[0008] The technical solution of the present invention is as follows:

[0009] A method for preparing a Janus photothermal layer comprises the following steps:

[0010] Mixing LiF and HCl to obtain a mixed solution;

[0011] Add Ti to the mixture 3 AlC 2precursor, and obtain a multilayer MXene suspension;

[0012] In an inert gas atmosphere, the multilayer MXene suspension was subjected to ultrasonic exfoliation and centrifugal treatment to obtain a single layer of Ti 3 C 2 T x MXene;

[0013] The fabric is immersed in the single layer of Ti 3 C 2 T x In MXene, a photothermal prefabricated layer is obtained;

[0014] A hydrophobic modifier is coated on one side of the photothermal prefabricated layer, and after drying, a Janus photothermal layer is obtained.

[0015] The method for preparing the Janus photothermal layer, wherein Ti is added to the mixed solution 3 AlC 2 , the steps of obtaining a multilayer MXene suspension specifically include:

[0016] The Ti 3 AlC 2 The precursor is divided into several portions, and is sequentially added into the mixed solution at predetermined time intervals under a constant temperature water bath condition to obtain a mixture;

[0017] The mixture is subjected to heat preservation stirring and centrifugal washing treatment in a constant temperature water bath to obtain a multilayer MXene suspension.

[0018] The method for preparing the Janus photothermal layer, wherein the temperature of the constant temperature water bath condition is 33-37° C.; the time of the heat preservation and stirring is 40-56 hours.

[0019] The method for preparing the Janus photothermal layer, wherein the predetermined time is 1-2 minutes; and the centrifugal speed of the centrifugal washing treatment is 3200-3800 rpm.

[0020] The method for preparing the Janus photothermal layer, wherein the rotation speed of the centrifugal treatment is 11000-13000 rpm, and the time of the centrifugal treatment is 25-35 min.

[0021] The method for preparing the Janus photothermal layer, wherein the drying temperature of the drying treatment is 75-85° C., and the drying time of the drying treatment is 2.5-3.5 hours.

[0022] The preparation method of the Janus photothermal layer, wherein the hydrophobic modifier is one of PDMS solution, triethoxyoctadecylsiloxane, and stearic acid.

[0023] A Janus photothermal layer is prepared by using the preparation method of the Janus photothermal layer.

[0024] An evaporator comprises a first support frame, a second support frame and a Janus photothermal layer; the first support frame and the second support frame are symmetrically arranged, and two ends of the Janus photothermal layer are respectively fixed to the first support frame and the second support frame; the Janus photothermal layer presents a suspension bridge-type suspended structure.

[0025] The evaporator is used for solar seawater desalination.

[0026] Beneficial effect: The present invention provides a Janus photothermal layer and a preparation method thereof, and an evaporator. The preparation method comprises the steps of: mixing LiF and HCl to obtain a mixed solution; adding Ti to the mixed solution; 3 AlC 2 precursor to obtain a multilayer MXene suspension; under inert gas conditions, the multilayer MXene suspension is ultrasonically exfoliated and centrifuged to obtain a single layer Ti 3 C 2 T x MXene; soak the fabric in the monolayer Ti 3 C 2 T x MXene, a photothermal prefabricated layer is obtained; a hydrophobic modifier is coated on one side of the photothermal prefabricated layer, and after drying, a Janus photothermal layer is obtained. 3 AlC 2 Precursor etching followed by ultrasonic stripping to obtain a single layer of Ti 3 C 2 T x MXene; then the hydrogen bonding effect of MXene is used to firmly adsorb MXene on the fabric, and then one side of the fabric is hydrophobically modified using a hydrophobic modifier to construct a Janus structure photothermal layer with asymmetric wettability, which has excellent light absorption and photothermal conversion capabilities; in addition, by constructing an evaporator with a suspension bridge structure using the Janus photothermal layer, it can be used for solar seawater desalination; and the constructed suspension bridge structure has good thermal management capabilities, the evaporator can achieve efficient solar seawater desalination, and has good stability in long-term desalination operation, and can collect salt crystals while producing clean water. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a process flow chart of a Janus photothermal layer preparation method of the present invention;

[0028] Figure 2 Schematic diagram of the preparation process of the Janus photothermal layer for efficient photothermal conversion in Example 1;

[0029] Figure 3 This is a dynamic water contact angle test diagram of CFMP2 in Example 1;

[0030] Figure 4 UV-visible-near-infrared absorption spectra of CF, CFM1, CFM2, CFM3 and CFMP2;

[0031] Figure 5 The temperature changes and infrared thermal images of CF, CFM2 and CFMP2 under sunlight;

[0032] Figure 6 For CF, CFM1, CFM2, CFM3 and CFMP2 evaporators in water, using 1 kW / m 2 The light intensity was irradiated for 1 h, and the data graph of evaporation rate and evaporation efficiency of the evaporator was calculated;

[0033] Figure 7 The ion concentration data of CFMP2 evaporator after desalination of 3.5 wt.% simulated seawater and actual seawater;

[0034] Figure 8 This is the feedback diagram of the long-term operation stability and salt crystallization of the CFMP2 evaporator in brine. DETAILED DESCRIPTION

[0035] The present invention provides a Janus photothermal layer and a preparation method thereof, and an evaporator. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0037] like Figure 1 As shown, the present invention provides a method for preparing a Janus photothermal layer, comprising the steps of:

[0038] Step S10: mixing LiF and HCl to obtain a mixed solution;

[0039] Step S20: Add Ti to the mixed solution 3 AlC 2 precursor, and obtain a multilayer MXene suspension;

[0040] Step S30: Under inert gas conditions, the multilayer MXene suspension is subjected to ultrasonic exfoliation and centrifugal treatment to obtain a single layer of Ti 3 C 2 T x MXene;

[0041] Step S40: Soaking the fabric in the single layer of Ti 3 C 2 T x In MXene, a photothermal prefabricated layer is obtained;

[0042] Step S50: coating a hydrophobic modifier on one side of the photothermal prefabricated layer, and obtaining a Janus photothermal layer after drying.

[0043] In this embodiment, by etching Ti 3 AlC 2 Precursor preparation of single-layer Ti 3 C 2 T x MXene is firmly adsorbed on the fabric by utilizing the hydrogen bonding effect of MXene, and then one side of the fabric is hydrophobically modified by utilizing a hydrophobic modifier, so that the two symmetrical surfaces of the Janus photothermal layer have a Janus structure with asymmetric wettability. The obtained Janus photothermal layer has excellent light absorption and photothermal conversion capabilities, and by limiting the width of the bottom hydrophobic layer, salt crystals are produced locally in the photothermal layer, and salt crystals can be collected while producing clean water.

[0044] Specifically, the single layer Ti 3 C 2 T xMXene has excellent light absorption capacity in the entire solar spectrum, and its metal-like properties can produce a localized plasma resonance effect, and has a high light absorption capacity in the near-infrared light range. Therefore, MXene is adsorbed on the fabric through the hydrogen bonding of MXene, so that the prepared photothermal layer has excellent light absorption and high photothermal conversion efficiency. In addition, one side of the fabric is hydrophobically modified using a hydrophobic modifier, so that the photothermal layer has a Janus structure. The photothermal layer with a Janus structure is used to solve the problem of salt crystallization in solar seawater desalination, and the evaporation of seawater can occur at the hydrophobic and hydrophilic interface of the Janus photothermal layer. Salt will continue to dissolve in the body water below the interface between the hydrophilic layer and the hydrophobic layer, and will not accumulate on the surface of the membrane through the hydrophobic layer. Therefore, the Janus photothermal layer has broad application prospects in solving salt precipitation.

[0045] In some embodiments, in step S10, the usage ratio of LiF to HCl is 1 g LiF: 20 mL 9M HCl.

[0046] In some embodiments, in step S20, Ti is added to the mixed solution. 3 AlC 2 , the steps of obtaining a multilayer MXene suspension specifically include:

[0047] Step S21: 3 AlC 2 The precursor is divided into several portions, and is sequentially added into the mixed solution at predetermined time intervals under a constant temperature water bath condition to obtain a mixture;

[0048] Step S22: The mixture is subjected to heat preservation, stirring, centrifugal washing treatment in a constant temperature water bath to obtain a multilayer MXene suspension.

[0049] In this embodiment, by 3 AlC 2 The precursor is divided into several portions, and then added to the mixed solution in sequence at predetermined time intervals, so that the Ti 3 AlC 2 The precursors are fully mixed in the mixed solution, which is conducive to etching. And by keeping warm and stirring under constant temperature water bath conditions, Ti 3 AlC 2 The precursor is etched more fully, and after centrifugal washing, the pH value of the multilayer MXene suspension is neutral.

[0050] In some embodiments, the temperature of the constant temperature water bath is 33-37°C; the time of the heat preservation and stirring is 40-56h. In the constant temperature water bath of 33-37°C, the mixed solution can be 3 AlC 2 The etching of the precursor is carried out more fully and the etching efficiency is improved.

[0051] In a preferred embodiment, the temperature of the constant temperature water bath is 35° C.; and the time of the heat preservation and stirring is 48 hours.

[0052] In some embodiments, the predetermined time is 1-2 min; and the centrifugal speed of the centrifugal washing treatment is 3200-3800 rpm.

[0053] Specifically, Ti was divided into several portions at intervals of 1-2 minutes. 3 AlC 2 The precursors are added to the mixed solution in sequence, so that Ti 3 AlC 2 The precursors are fully mixed in the mixed solution, which is beneficial to the Ti 3 AlC 2 Sufficient etching of the precursor.

[0054] In some preferred embodiments, washing is performed using deionized water at 3500 rpm to obtain a multilayer MXene suspension with a neutral pH value.

[0055] In some embodiments, the inert gas is selected from, but not limited to, one or more of nitrogen, helium, and argon.

[0056] In some embodiments, in step S30, the rotation speed of the centrifugal treatment is 11000-13000 rpm, and the time of the centrifugal treatment is 25-35 min.

[0057] In a preferred embodiment, the rotation speed of the centrifugal treatment is 12000 rpm, and the time of the centrifugal treatment is 30 min.

[0058] Specifically, the multilayer MXene suspension was subjected to ultrasonic exfoliation under Ar protection conditions, and then centrifuged at 12000 rpm for 30 min using a centrifuge; finally, the supernatant in the centrifuge tube was collected to obtain the single-layer Ti 3 C 2 T x MXene.

[0059] In some embodiments, in step S40, the single layer Ti 3 C 2 T xThe solid content of MXene is 12-20 mg / mL; the fabric is immersed in the single layer of Ti 3 C 2 T x Before MXene, the monolayer Ti 3 C 2 T x MXene and water are diluted in a certain volume ratio to obtain a dilution solution; then the single layer Ti 3 C 2 T x The MXene is immersed in the diluent for 10-30 minutes, and then removed and dried to obtain the photothermal prefabricated layer.

[0060] In some embodiments, the single layer Ti 3 C 2 T x The solid content of MXene is 16 mg / mL; the single layer Ti 3 C 2 T x The immersion time of MXene in the diluent is 10 min; the single layer Ti 3 C 2 T x The dilution ratio of MXene to water is 1:4. Under this parameter, the Janus photothermal layer has the highest light absorption rate, the best photothermal conversion performance, and the best evaporator performance.

[0061] In some embodiments, in step S50, the drying temperature of the drying process is 75-85° C., and the drying time of the drying process is 2.5-3.5 hours. At the temperature and time of the drying process, the curing of PDMS can be accelerated.

[0062] In a preferred embodiment, the drying temperature of the drying treatment is 80° C., and the drying time of the drying treatment is 3 hours.

[0063] Specifically, the photothermal prefabricated layer was moistened with water and then spread flat, and then the hydrophobic modifier was evenly coated on one side of the photothermal prefabricated layer, and then placed in a fume hood for 20 minutes to allow the n-hexane to evaporate; finally, it was placed in a vacuum oven at 80° C. for 3 hours to obtain a Janus photothermal layer.

[0064] In some embodiments, the hydrophobic modifier is one of, but not limited to, PDMS solution, triethoxyoctadecylsiloxane (ODS), and stearic acid; wherein the PDMS solution is prepared by mixing PDMS, a curing agent, and n-hexane.

[0065] Specifically, 1 g of PDMS and 0.1 g of curing agent were added into 10 mL of n-hexane and stirred for 10 min to obtain the PDMS solution, which was the hydrophobic modifier.

[0066] In some embodiments, the fabric is selected from but not limited to one or more of cotton fabric and cotton-based fabric, so that MXene can be adsorbed on the fabric through hydrogen bonding, thereby improving light absorption and light-to-heat conversion efficiency.

[0067] In addition, the present invention also provides a Janus photothermal layer, which is prepared using the preparation method of the Janus photothermal layer.

[0068] In this embodiment, the Janus photothermal layer has an asymmetric wettability Janus structure and is combined with a single layer of Ti adsorbed on the fabric by hydrogen bonding. 3 C 2 T x MXene can effectively improve the light absorption efficiency and photothermal conversion capacity of the Janus photothermal layer. When used in an evaporator, salt crystals can be generated locally in the photothermal layer by limiting the width of the bottom hydrophobic layer, and salt crystals can be collected while producing clean water.

[0069] In addition, the present invention also provides an evaporator, including a first support frame, a second support frame and a Janus photothermal layer; the first support frame and the second support frame are symmetrically arranged, and the two ends of the Janus photothermal layer are respectively fixed to the first support frame and the second support frame; the Janus photothermal layer presents a suspension bridge-type suspended structure.

[0070] In this embodiment, the evaporator with a suspension bridge structure has good thermal management capabilities. The evaporator can achieve efficient solar desalination of seawater and has good stability in long-term desalination operation. It can collect salt crystals while producing clean water.

[0071] In some embodiments, the evaporator is used for solar desalination.

[0072] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0073] Example 1

[0074] This embodiment prepares a Janus photothermal layer and evaporator with high efficiency photothermal conversion, such as Figure 2 As shown, the specific steps include:

[0075] Step S1: 1 g of LiF was added to 20 mL of HCl (9 M) and stirred for 20 minutes until LiF was completely dissolved to obtain a LiF / HCl solution;

[0076] Step S2: 1g Ti 3 AlC 2 The precursor was divided into 5 equal parts and added to the LiF / HCl solution at 1-min intervals. During this period, the polytetrafluoroethylene container was placed in a 35°C water bath. 3 AlC 2 After the precursor, the reaction device was placed in a water bath at 35°C for 48 hours of heat preservation and stirring; after the reaction, it was centrifuged and washed with deionized water at 3500 rpm until the pH value was neutral to obtain a multilayer MXene suspension;

[0077] Step S3: The multilayer MXene suspension is subjected to ultrasonic exfoliation under Ar protection conditions, and then centrifuged at 12000 rpm for 30 min using a centrifuge; finally, the supernatant in the centrifuge tube is collected as the single-layer Ti 3 C 2 T x MXene;

[0078] Step S4: Cut 16×5 cm 2 4 mL of a single layer of Ti with a solid content of 16 mg / mL was taken from the cotton fabric (CF). 3 C 2 T x MXene and water were diluted in a volume ratio of 1:4 to obtain a diluent; the cotton fabric was then immersed in the diluent for 10 min, and then removed and dried naturally to obtain a photothermal prefabricated layer, recorded as CFM 2;

[0079] Step S5: Weigh 1 g of PDMS and 0.1 g of curing agent and add them to 10 mL of n-hexane, stir for 10 min to obtain a PDMS solution. Wet CFM 2 with water and spread it on aluminum foil. Use a brush to evenly apply the PDMS solution on one side of CFM 2, and then place it in a fume hood for 20 min to evaporate the n-hexane. Finally, place CFM 2 in a vacuum oven at 80 °C for 3 h to obtain a Janus photothermal layer, recorded as CFMP 2.

[0080] Finally, two liquid reservoirs are used as the first support frame and the second support frame respectively, and the two ends of the Janus thermal layer are hung on the container wall of the liquid storage container, and the two ends of the Janus thermal layer are in contact with the liquid in the liquid reservoir to obtain an evaporator with a suspension bridge structure (with the hydrophobic surface facing upward).

[0081] Comparative Example 1

[0082] Untreated cotton fabric was used as the photothermal layer, denoted as CF; CFM 1 and CFM 3 were 4 mL of a single layer of Ti with a solid content of 16 mg / mL. 3 C 2 T x The photothermal layer was obtained by diluting MXene and water in a volume ratio of 1:16 and 1:2. The other treatment processes were consistent with CFM 2.

[0083] Similarly, the first support frame and the second support frame are used to fix the two ends of the photothermal layer at the ends of the first support frame and the second support frame to form a suspension bridge structure to obtain an evaporator.

[0084] In order to verify the performance of the photothermal layer and evaporator prepared in Example 1 and Comparative Example 1, various performance tests were performed on them, as follows:

[0085] 1. In order to verify whether the Janus structure of the evaporator is successfully prepared, the dynamic water contact angle test is carried out on the front and back sides of CMFP 2. Figure 3 It can be seen that there is a significant difference in the hydrophilicity of the front and back sides of CFMP 2. Due to the introduction of MXene with rich functional groups and the presence of the hydrophilic cotton fabric itself, the hydrophilic side of CFMP 2, that is, the side not modified by the hydrophobic matrix PDMS, has good hydrophilicity, and the water droplet completely diffuses within 10 seconds after dripping. On the hydrophobic side, that is, the side loaded with PDMS, the water droplet always stays on the surface of the material with a contact angle of 150°. Therefore, the Janus structure CFMP with asymmetric wettability was successfully prepared.

[0086] 2. The ultraviolet, visible and near-infrared light absorption rates of the photothermal layers prepared in Example 1 and Comparative Example 1 were tested.

[0087] The light absorption rate is given by the formula (R represents the light reflectivity of the photothermal layer, and T represents the light transmittance of the photothermal layer) is given.

[0088] It can be seen that under the same test conditions, Figure 4 It can be seen that the light absorption rate of CFMP2 can reach 90%, while that of CF is only 40%.

[0089] 3. The temperature changes and infrared thermal imaging of CF, CFM2 and CFMP2 under sunlight are as follows: Figure 5 As shown, it can be seen that CFM2 and CFMP2 have a fast photothermal response. After 1 min of irradiation, the surface temperature rises rapidly, while the surface temperature of the blank cotton fabric in comparison does not change significantly, indicating that the loading of MXene makes CFM2 and CFMP2 have a fast photoresponse and converts the absorbed light into heat.

[0090] 4. The evaporators prepared in Example 1 and Comparative Example 1 were used to perform solar evaporation on water. A xenon lamp was used to simulate sunlight, and the light intensity was 1 kW / m 2 .

[0091] The evaporation rate is given by the formula (Δm (kg) represents the mass change of the evaporation system, t (h) represents the evaporation time, S (m 2 ) is the effective evaporation area of ​​the evaporator.

[0092] The results are as follows Figure 6 As shown in the figure, under the same test conditions, the evaporation rate of the evaporator made by CFMP2 is 1.5 kg·m -2 ·h -1 However, the evaporator made of CF has an evaporation rate of only 0.71 kg·m due to the lack of photothermal materials. -2 ·h -1 .

[0093] 5. ICP-OES was used to test the ion concentration of simulated seawater, actual seawater and collected condensed water to explore the removal effect of the evaporator on salt ions. As shown in Figure 7, whether it is simulated seawater or actual seawater, the ion concentration of the condensed water after desalination by the evaporator is lower than 10 mg / L, which is a decrease of 10 orders of magnitude, indicating that the evaporator has excellent desalination performance.

[0094] 6. The long-term operation stability and salt crystallization of the evaporator prepared in Example 1 were tested in salt water. Under 1 sun illumination, 20 wt.% NaCl solution was used as the evaporating liquid for desalination. 12 h per day was used as a cycle, and 8 cycles were performed continuously. The evaporation rate of the evaporator is shown in Figure 8. After 8 cycles, the average evaporation rate of the evaporator can still be maintained at 1.35 kg·m -2 ·h -1 There is no obvious decrease, which verifies the cycle stability of CFMP2. It can be seen that many salt crystals are generated at the edge of the evaporator. Finally, these salt crystals are collected and weighed to 25 g. The daily salt production is 1.56 kg / m 2 Therefore, the constructed evaporator can obtain salt while producing clean water, which provides new application prospects for seawater desalination technology.

[0095] In summary, the present invention provides a Janus photothermal layer and a preparation method thereof, and an evaporator. The preparation method comprises the steps of: mixing LiF and HCl to obtain a mixed solution; adding Ti to the mixed solution; 3 AlC 2precursor to obtain a multilayer MXene suspension; under inert gas conditions, the multilayer MXene suspension is ultrasonically exfoliated and centrifuged to obtain a single layer Ti 3 C 2 T x MXene; soak the fabric in the monolayer Ti 3 C 2 T x MXene, a photothermal prefabricated layer is obtained; a hydrophobic modifier is coated on one side of the photothermal prefabricated layer, and after drying, a Janus photothermal layer is obtained. 3 AlC 2 Precursor etching followed by ultrasonic stripping to obtain a single layer of Ti 3 C 2 T x MXene; then the hydrogen bonding effect of MXene is used to firmly adsorb MXene on the fabric, and then one side of the fabric is hydrophobically modified using a hydrophobic modifier to construct a Janus structure photothermal layer with asymmetric wettability, which has excellent light absorption and photothermal conversion capabilities; in addition, by constructing an evaporator with a suspension bridge structure using the Janus photothermal layer, it can be used for solar seawater desalination; and the constructed suspension bridge structure has good thermal management capabilities, the evaporator can achieve efficient solar seawater desalination, and has good stability in long-term desalination operation, and can collect salt crystals while producing clean water.

[0096] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a Janus photothermal layer, characterized in that: Includes steps: Mixing LiF and HCl to obtain a mixed solution; Adding a Ti3AlC2 precursor to the mixed solution to obtain a multilayer MXene suspension; In an inert gas atmosphere, the multilayer MXene suspension was subjected to ultrasonic exfoliation and centrifugal treatment to obtain a single-layer Ti3C2T x MXene; The single layer Ti3C2T x MXene and water were mixed in a volume ratio of 1:4 to obtain a single layer of Ti3C2T x MXene dilution solution, soak the fabric in the monolayer Ti3C2T x MXene dilution, a photothermal prefabricated layer is obtained; the single layer Ti3C2T x The solid content of MXene is 16 mg / mL; A PDMS solution is coated on one side of the photothermal prefabricated layer, and after drying, a Janus photothermal layer is obtained.

2. The method for preparing a Janus photothermal layer according to claim 1, characterized in that: The step of adding a Ti3AlC2 precursor to the mixed solution to obtain a multilayer MXene suspension specifically comprises: Dividing the Ti3AlC2 precursor into several portions, and sequentially adding the portions into the mixed solution at predetermined time intervals under a constant temperature water bath condition to obtain a mixture; The mixture is subjected to heat preservation stirring and centrifugal washing treatment in a constant temperature water bath to obtain a multilayer MXene suspension.

3. The method for preparing a Janus photothermal layer according to claim 2, characterized in that: The temperature of the constant temperature water bath is 33-37°C; the time of the heat preservation and stirring is 40-56h.

4. The method for preparing a Janus photothermal layer according to claim 2, characterized in that: The predetermined time is 1-2 minutes; the centrifugal speed of the centrifugal washing treatment is 3200-3800 rpm.

5. The method for preparing a Janus photothermal layer according to claim 1, characterized in that: The rotation speed of the centrifugal treatment is 11000-13000 rpm, and the time of the centrifugal treatment is 25-35 min.

6. The method for preparing a Janus photothermal layer according to claim 1, characterized in that: The drying temperature of the drying treatment is 75-85° C., and the drying time of the drying treatment is 2.5-3.5 hours.

7. A Janus photothermal layer, characterized in that: The Janus photothermal layer is prepared by the preparation method of any one of claims 1 to 6.

8. An evaporator, characterized in that: It comprises a first support frame, a second support frame and the Janus photothermal layer as claimed in claim 7; the first support frame and the second support frame are symmetrically arranged, and the two ends of the Janus photothermal layer are respectively fixed to the first support frame and the second support frame; the Janus photothermal layer presents a suspension bridge-type suspended structure.

9. The evaporator according to claim 8, characterized in that The evaporator is used for solar seawater desalination.

Citation Information

Patent Citations

  • Seawater desalination evaporator based on MXene modified honeycomb fabric, and preparation method thereof

    CN113735208A

  • Janus type composite foam photo-thermal functional material as well as preparation method and application thereof

    CN115491020A